(untitled) (American Journal of Islam and Society, 1989)
Let us start with the title of the book. Its first part is hardly exciting. Several sociology publications currently carry similar titles: New Horizons in Sociology, New Directions in Sociology, New Debates in Sociology, or merely New Sociology. It seems that most people writing about sociology these days must write something new or not write at all. What is new about this book can be seen from the second part of its tille, A Physico-Chemical Approach 10 Human Behavior-eye-catching, even startling. There have been organic, evolutionary, and ecological analogies used by sociologists in the past, often with great success. However, physicochemical analogy is something else. If, by using this title. Dr. Beg had in mind to shock sociologists into reading his book from cover to cover, he must be congratulated, for, no doubt, the title is intriguing, to say the least. The contents do not reveal too much about the book. However, they must not be taken lightly. Wi.lson (1975) produced yet another "new" and asserted that human values, even customs and traditions, are genetically transmitted from one generation to another. Since then, he has won a number of adherents to his point of view. So here it is: a physico-chemical approach to sociology. If Harvard publishes treatises like Wilson’s Sociobiology, how can we reject Hamdard’s New Dimensions as being out of hand? After all , Wilson is a zoologist with hardly a flair for sociology in his dossier. The author of this book, Mirza Arshad Ali Beg, is a trained and experienced chemist with graduate degrees from Karachi (MSc.) and British Columbia (Ph.D.). He began in 1941 as a senior research officer at the Pakistan Council of Scientific and Industrial Research (PCSIR) and in 1985 became the director of its facilities in Karachi. Since then, he has been promoted to the secretarial rank in this organization. Dr. Beg has also held several important posts in national and international organizations. Apparently, Dr. Beg is a qualified, experienced researcher in chemistry. As such, it is to his credit that in this book he has ventured far afield from his area of specialization. This book is a testimony to the fact that sociology is not, has not been, and must not be the exclusive domain of sociologists. All throughout its relatively brief history, sociology has benefitted from the contributions of historians, philosophers, psychologists, even engineers. Thus, if a chemist is trying his hand this time, we must not be too shocked ...